2007
DOI: 10.1007/bf03178434
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results of entrance dose in vivo dosimetry for high energy photons in external beam radiotherapy using MOSFETs

Abstract: Thomson and Nielsen TN-502 RD MOSFETs were used for entrance dose in vivo dosimetry for 6 and 10 MV photons. A total of 24 patients were tested, 10 breast, 8 prostate, 5 lung and 1 head and neck. For prostates three fields were checked. For all other plans all fields were checked. An action threshold of 8% was set for any one field and 5% for all fields combined. The total number of fields tested was 56, with a mean discrepancy of 1.4% and S.D. of 2.6%. Breasts had a mean discrepancy of 1.8% and S.D. of 2.8%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…This means that the system is reproducible with respect to each TPS. This result is similar to those found in other institutions [5,24] using other measurement devices like different MOSFET or diode based dosimeters.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This means that the system is reproducible with respect to each TPS. This result is similar to those found in other institutions [5,24] using other measurement devices like different MOSFET or diode based dosimeters.…”
Section: Discussionsupporting
confidence: 91%
“…This part of the study was aimed at establishing an Action Threshold (AT) [5,24], defined as the maximum accepted discrepancy between the dose measured with the detector and the dose calculated with the TPS for a single field (in our procedure only one field at a time is verified). A single AT has been established, one specific for breast and one for prostate treatments, from the analysis of the tests in phantoms, and it has been used as an indicator of the correctness of breast and prostate treatments themselves.…”
Section: Methodsmentioning
confidence: 99%
“…As such, MOSFET detectors are finding applications in radiotherapy radiation dosimetry [9][10][11][12][13][14][15][16] . They have also been used commonly for in-vivo dosimetry [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…The anisotropy of the MOSFET, as for other in-vivo dosimeters may be explained by the attenuation caused by the geometry of the detector and has been estimated at between 1% and 3 % from 0° to 180° for the most recent models TN-502-RD [17,28,29]. Therefore, when the angle of the beam is 0 ° to 25 ° on entry and between 0 ° to 30 ° at exit, the angular dependence may be considered as negligible.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MOSFETs could be suitable for in-vivo assessment of radiosurgery microbeams [7,6,8]. In the literature their use has been described extensively for such in vivo procedures as: in vivo dosimetry for external radiotherapy [9,10,11], dose verification in intensity modulated radiotherapy (IMRT) [12,13,14], measurements in head and neck Tomotherapy [15], skin dose measurement [16], entry dosimetry [17], implantable detectors for in-situ testing during radiation therapy treatment [18], dose verification of permanent low-dose-rate implants [19] and as a dosimeter for imaging in radiological procedures [20]. Additional studies have reported excellent linearity, dosimetric accuracy in the build-up region and directional independence [9,21].…”
Section: Introductionmentioning
confidence: 99%